2016
DOI: 10.3832/ifor1370-008
|View full text |Cite
|
Sign up to set email alerts
|

Ectomycorrhizal fungal community associated with autochthonous white poplar from Serbia

Abstract: We analyzed the community of ectomycorrhizal fungi of an autochthonous white poplar (Populus alba L.) stand in the Kovilj-Petrovaradin marshes (Serbia), and examined its seasonal dynamics. Ectomycorrhizal types were identified by combining morphological and anatomical descriptions with molecular methods (sequencing of ITS region of ribosomal DNA). In two seasons, 20 ectomycorrhizal types were recorded, from which 11 types were identified to the species level, six were determined to the genus level, two types w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 36 publications
2
4
0
Order By: Relevance
“…2, Entoloma sp., Cenococcum sp., Unknown types K3 and T1; other morphotypes constituted less than 3% of the entire ectomycorrhizal community. Thus, it is clear that the ectomycorrhizal community associated with spruce from the examined sites in Serbia consisted of few abundant and numerous infrequent ectomycorrhizal types, which is in accordance with previous studies (Karlinski & Kieliszewska-Rokicka 2004, De Roman & De Miguel 2005, Katanić et al 2015. Wang et al (2015) investigated the ectomycorrhizal community structure on Picea abies at the tree line in the Austrian Alps; they found that at the higher altitude the ectomycorrhizal community was dominated by Cortinarius sp., whereas at the lower elevation site the community was dominated by Russula.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…2, Entoloma sp., Cenococcum sp., Unknown types K3 and T1; other morphotypes constituted less than 3% of the entire ectomycorrhizal community. Thus, it is clear that the ectomycorrhizal community associated with spruce from the examined sites in Serbia consisted of few abundant and numerous infrequent ectomycorrhizal types, which is in accordance with previous studies (Karlinski & Kieliszewska-Rokicka 2004, De Roman & De Miguel 2005, Katanić et al 2015. Wang et al (2015) investigated the ectomycorrhizal community structure on Picea abies at the tree line in the Austrian Alps; they found that at the higher altitude the ectomycorrhizal community was dominated by Cortinarius sp., whereas at the lower elevation site the community was dominated by Russula.…”
Section: Discussionsupporting
confidence: 85%
“…According to previous studies (De Roman & De Miguel 2005, Katanić et al 2015, we found no significant differences between the spring and autumn in the number of ectomycorrhizal types and vital ectomycorrhizal root tips, as well as in diversity indices. However, the total number of fine roots was greater in the spring compared with the autumn because of the higher number of old, non-turgescent and nonmycorrhizal roots present in the spring, which could be explained by the seasonal influence on fine roots.…”
Section: Comparison Of Two Seasonssupporting
confidence: 53%
“…After two months of mycelial culture, ITS sequences were acquired by amplifying the DNA of the mycelium, followed by BLAST alignment in GenBank. The S1 (OM846602), S2 (OM846601), and R1 (OL339344) ITS sequences showed 99.69%, 99.32%, and 100% homology with those of the Chinese S. bovinus , S. luteus , and R. sinensis specimens, respectively [ 28 30 ]. The S3 ITS sequence (OM865366) showed 99.03% homology with that of Japanese S. grevillea [ 31 ].…”
Section: Resultsmentioning
confidence: 99%
“…The molecular analysis of EM roots indicated that the EM fungal communities of S. caprea from the sites contained a diverse and broad array of fungi, including basidiomycetes and ascomycetes. Well-known fungal associates of the members of the Salicaceae (Salix and Populus) are, for example, Lactarius controversus, Russula atrorubens, Russula persicina, and Tricholoma cingulatum [24,52]. Many species of Cortinarius [53,54] and Hebeloma [55] also preferentially associate with members of the Salicaceae family.…”
Section: Discussionmentioning
confidence: 99%